(untitled) (Applied Biological Research, 2015)
The study was aimed to assess the effect of different levels of paclobutrazol and summer pruning on fruit quality of apple cv. ‘Red Delicious’. The experiment was conducted at SKUAST-K, Shalimar (J&K) during 2012 and 2013 on apple trees of >15 years age, spaced at 5.49 × 5.49 m distance. The experiment was laid in a completely randomized block design with paclobutrazol spray tested at 3 concentrations (250, 500 and 750 ppm) and summer pruning at 2 timings (8 and 12 weeks after full bloom) and their combinations. Highest yield of 101.0 kg tree-1 was obtained in treatment 750 ppm paclobutrazol + 2 summer prunings in comparison to control. In addition, it significantly improved fruit size (53.15 cm), weight (188.19 g), volume (188.12 cm3), colour change (3.40 score), firmness (11.98 kg cm-2), organoleptic rating in terms of taste (3.14 score), texture (3.24 score), flavour (3.12 score) and total soluble solids (14.47oB) whereas acidity (0.23%) was reduced in comparison to control and other treatments during both the years.